Sporting hats and national symbolism: The Kangol beret and the London Olympic Games of 1948. Issue 2 (1st March 2014) - Biddle-Perry, Geraldine
This article explores the British Olympic Association's adoption of the Kangol beret for both male and female athletes at the London Games of 1948. The Games represented a critical juncture in both Olympic and British political history. The article outlines the fashion historical development of the 'Anglo-Basque' beret as a context for examining how the beret came to function as the symbolic embodiment of shifting concepts of British sporting nationalism within the Olympic arena. In World War II the beret became synonymous with Lord Montgomery of Alamein (Monty), and by extension the fighting spirit of the British nation. The article questions to what extent the choice of the 'Monty' beret in London in 1948 can be seen as both a response to the Berlin Olympics in 1936 and the wider contemporary context of a nation at the crossroads between austerity and affluence, and new demands for wider democratic freedom and welfare reform.